Aging and Work Ability: The Moderating Role of Job and Personal Resources - Converso, Daniela; Sottimano, Ilaria; Guidetti, Gloria; Loera, Barbara; Cortini, Michela; Viotti, Sara (Frontiers in Psychology, 2018)
Objective: Demographic changes involving western countries and later retirements due to the recent pension reforms induce a gradual aging of the workforce. This implies an increasing number of workers with health problems and a decreasing of ability to work. In this direction, the present study aims at examining the role of job and personal resources between age and work ability within nurses. Method: The study was cross-sectional and not randomized; data were collected by a self-report questionnaire during a multi-center survey conducted in two Italian hospitals in 2016. In this way, 333 nurses were reached. Results: Multiple linear regression showed that age is significantly and negatively associated to work ability, and that job resources (e.g., decision authority and meaning of work) and personal resources (e.g., hope and resilience) moderate the relationship between age and work ability. Discussion: These results highlight that investing in work and personal resources to support WA is even more relevant for those professions where high physical effort is required.